EFISIENSI PENGELUARAN PEMERINTAH BIDANG PENDIDIKAN DI INDONESIA (DATA ENVELOPMENT ANALYSIS) - Tomi Mandala Putra; Merri Anitasari (Universitas Bengkulu, 2019)
This study aims to determine the Level of Efficiency in Education Expenditures in 34 provinces in Indonesia. The type of data used in this study is the cross-section data for 2017. The use of budget input as an input variable and student-teacher ratio (RGM) as an output variable. This study uses descriptive analysis with analysis of Data Envelopment Analysis using the assumption of the Return to Scale (VRS) variable and the model used for input (input-oriented) input. The results of this study indicate that the general facts of large provinces in Indonesia are still very few that reach the level of efficiency in technical costs. Already 3 provinces have achieved efficiently. This proves there is still waste in education spending suggestions that can be submitted in this study about the local government to evaluate the use of education which must be adjusted to the number of teacher and student ratios in each region so there is no need to waste and local government can improve. Keywords: Efficiency, Education Expenditures, Data Envelopment Analysis, Cost Technical